2005
DOI: 10.1073/pnas.0500485102
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inducible nitric oxide synthase by aggresome formation

Abstract: Misfolding and aggregation of proteins play an important part in the pathogenesis of several genetic and degenerative diseases. Recent evidence suggests that cells have evolved a pathway that involves sequestration of aggregated proteins into specialized ''holding stations'' called aggresomes. Here we show that cells regulate inducible NO synthase (iNOS), an important host defense protein, through aggresome formation. iNOS aggresome formation depends on a functional dynein motor and the integrity of the microt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 30 publications
(54 reference statements)
3
70
0
Order By: Relevance
“…Recent evidence suggests that aggresome formation is also a physiologic mechanism to regulate certain cellular proteins. The latter process, termed ''physiologic aggresome,'' has been described in connection to cellular regulation of iNOS (8,9). We have recently shown that iNOS is expressed initially as a cytosolic protein but is eventually targeted to a perinuclear location, identified by our data as an aggresome.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…Recent evidence suggests that aggresome formation is also a physiologic mechanism to regulate certain cellular proteins. The latter process, termed ''physiologic aggresome,'' has been described in connection to cellular regulation of iNOS (8,9). We have recently shown that iNOS is expressed initially as a cytosolic protein but is eventually targeted to a perinuclear location, identified by our data as an aggresome.…”
mentioning
confidence: 77%
“…In vivo, iNOS is expressed in states of inflammation and in response to proinflammatory cytokines (5,17). We have previously shown that cytokine-induced iNOS is targeted to the aggresome in various human and murine cell lines (8). In RT4 cells, an epithelial cell line in which iNOS production and iNOS aggresomes have been well characterized (16,18,19), iNOS aggresome formation becomes clearly evident 24 h following cytokine stimulation (8).…”
Section: Dar-4m Am Is a Reliable Indicator Of Subcellular No Productimentioning
confidence: 99%
See 3 more Smart Citations